Numerical Study of Thermal Efficiency in Light-Gauge Steel Panels Designed with Varying Insulation Ratios - Dilanka Chandrasiri; Perampalam Gatheeshgar; Hadi Monsef Ahmadi; Lenganji Simwanda (Buildings, 2024)
In the construction domain, there is a growing emphasis on sustainability, resource efficiency, and energy optimisation. Light-gauge steel panels (LGSPs) stand out for their inherent advantages including lightweight construction and energy efficiency. However, the effective management of thermal efficiency, particularly addressing thermal bridges, is crucial. This paper conducts a detailed numerical investigation into the thermal performance of LGSPs, examining varied insulation ratios. Thermal finite element (FE) models were initially developed using the THERM software and validated against code predictions and results available in the literature. A comprehensive parametric study explored different insulation ratios, insulation materials, and wall thicknesses, discovering their impact on thermal transmittance (U-value). Key findings revealed that U-value correlated with insulation material conductivity, with E-PLA insulation exhibiting the lowest values, and increasing wall thickness resulted in decreased U-values. It was found that a strategic use of insulation yielded a U-value reduction of over 65%. New simplified design approaches were developed, featuring insulation ratios linked to accurate U-value predictions for LGSP configurations. The new design approaches were found to provide more accurate and consistent U-value predictions. Moreover, optimum insulation ratios for new builds and existing building extensions were found to be around 0.9 and 0.7 for 275 mm and 325 mm thick walls, respectively. These proposed energy-efficient solutions, facilitated through advanced design, are well-aligned with net-zero construction objectives.